Cultural Hegemony of the Karo People in Building Tourism Brands on Instagram - Sinuhaji, Zahra Wulandari; Sazali, Hasan (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This article aims to explore the cultural hegemony of the Karo people in building their tourism brand on Instagram. The type of research used in this article is qualitative with a phenomenological approach. Through the analysis of content shared by the Karo community on Instagram, this study identifies patterns of dominance of Karo nature and culture images in efforts to promote their tourism destinations. The results of the study reveal that the cultural hegemony of the Karo people in building tourism brands on Instagram is based on three factors. These include the dominance of local culture representing the beauty of nature, culture, customs, and arts; the use of local language and terms; and the participation of the community in efforts to preserve the environment and utilize social media as a promotional tool as an impact of globalization and modernization in Karo tourism content on Instagram. Overall, this research provides deep insights into how the cultural hegemony of the Karo people influences the building of their tourism brand on Instagram.